Development and validation of a dosing nomogram for amoxicillin in infective endocarditis. (30th June 2020) - Rambaud, Antoine; Gaborit, Benjamin Jean; Deschanvres, Colin; Le Turnier, Paul; Lecomte, Raphaël; Asseray-Madani, Nathalie; Leroy, Anne-Gaëlle; Deslandes, Guillaume; Dailly, Éric; Jolliet, Pascale; Boutoille, David; Bellouard, Ronan; et al.
Abstract: Background: Amoxicillin is the first-line treatment for streptococcal or enterococcal infective endocarditis (IE) with a dose regimen adapted to weight. Objectives: Covariates influencing pharmacokinetics (PK) of amoxicillin were identified in order to develop a dosing nomogram based on identified covariates for individual adaptation. Patients and methods: Patients treated with amoxicillin administered by continuous infusion for IE were included retrospectively. The population PK analysis was performed using the Pmetrics package for R (NPAG algorithm). Influence of weight, ideal weight, height, BMI, body surface area, glomerular filtration rate adapted to the body surface area and calculated by the CKD-EPI method (mL/min), additional ceftriaxone treatment and serum protein level on amoxicillin PK was tested. A nomogram was then developed to determine the daily dose needed to achieve a steady-state free plasma concentration above 4× MIC, 100% of the time, without exceeding a total plasma concentration of 80 mg/L. Results: A total of 160 patients were included. Population PK analysis was performed on 540 amoxicillin plasma concentrations. A two-compartment model best described amoxicillin PK and the glomerular filtration rate covariate significantly improved the model when included in the calculation of the elimination constant Ke . Conclusions: This work allowed the development of a dosing nomogram that can help to increase achievement of the PK/pharmacodynamic targets in IE treated with amoxicillin.